Organotypic keratinocyte cocultures in defined medium with regular epidermal morphogenesis and differentiation - Stark, Hans-Jürgen; Breitkreutz, Dirk; Fusenig, Norbert (The journal of investigative dermatology, 2015)
Skin equivalents formed by keratinocytes cocultured with fibroblasts embedded in collagen lattices represent promising tools for mechanistic studies of skin physiology, for pharmacotoxicologic testing, and for the use as skin substitutes in wound treatment. Such cultures would be superior in defined media to avoid interference with components of serum or tissue extracts. Here we demonstrate that a defined medium (supplemented keratinocyte defined medium) supports epidermal morphogenesis in organotypic cocultures equally well as serum-containing medium (mixture of Ham’s F12 and Dulbecco’s modified Eagle’s medium), as documented by hallmarks of the epidermal phenotype studied by immunofluorescence and electron microscopy. In both cases regularly structured, orthokeratinized epithelia evolved with similar kinetics. Morphology in mixture of Ham’s F12 and Dulbecco’s modified Eagle’s medium was slightly hyperplastic, and keratins 1 and 10 synthesis less co-ordinated than in supplemented keratinocyte defined medium, but a consistently inverted sequence of expression of keratins 1 and 10 was found in either medium. The late differentiation markers filaggrin, involucrin, keratin 2e, and transglutaminase 1 corresponded in their typical distribution in upper suprabasal layers. Keratin 16 persisted under both conditions indicating the activated epidermal state. Keratinocyte proliferation was comparable in both media, whereas fibroblast multiplication and proliferation was delayed and reduced in supplemented keratinocyte defined medium. In both media, ultrastructural features of epidermal differentiation as well as reconstitution of a basement membrane occurred similarly. Immature lamellar bodies and cytoplasmatic vacuoles, however, indicated an impaired lipid metabolism in supplemented keratinocyte defined medium. Nevertheless, these defined organotypic cocultures provide a suitable basis for in vitro skin models to study molecular mechanisms of tissue homeostasis and for use in pharmacotoxicologic testing.
Gesehen am 11.02.2021